Diagnostic Accuracy of Plasma Ghrelin Concentrations in Pediatric Sepsis-Associated Acute Respiratory Distress Syndrome: A Single-Center Cohort Study - Yuan, Xiu; Li, Shaojun; Zhou, Liang; Tang, Tian; Cheng, Yuwei; Ao, Xiaoxiao; Tan, Liping (Frontiers in Pediatrics, 2021)
Background: Ghrelin is the endogenous ligand of growth hormone secretagogue receptor 1a, which plays a role in regulating immunity and inflammation. The aim of this study is to assess the diagnostic value of plasma ghrelin in sepsis-associated pediatric acute respiratory distress syndrome (PARDS). Methods: We recruited patients who were admitted to the pediatric ICU (PICU) of the Children's Hospital of Chongqing Medical University between January 2019 and January 2020 and met the diagnostic criteria for sepsis. Data on clinical variables, laboratory indicators, plasma ghrelin concentrations, and inflammatory factors were collected and evaluated, and patients were followed up for 28 days. The area under the receiver-operating characteristic curves (AUROC) were determined using logistic regression to calculate and test cut-off values for ghrelin as a diagnostic indicator of sepsis-associated PARDS. The log-rank test was used to compare survival according to ghrelin levels. Main results: Sixty-six PICU patients (30 with ARDS and 36 without ARDS) who met the diagnostic criteria of sepsis were recruited. The ghrelin level was significantly higher in the ARDS group than in the non-ARDS group. The AUROC of ghrelin was 0.708 (95% confidence interval: 0.584–0.833) and the positivity cutoff value was 445 pg/mL. Sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio of plasma ghrelin for the diagnosis of PARDS-associated sepsis were 86.7, 50.0, 59.1, 81.8, 1.734, and 0.266%, respectively. The survival rate of sepsis patients were significantly improved when the ghrelin level was >445 pg/mL. Conclusions: Ghrelin plasma levels were higher in sepsis-associated PARDS, and accompanied by increased levels of inflammatory factors. High ghrelin levels are a positive predictor of ICU survival in sepsis patients. Yet, there is no evidence to prove that elevated ghrelin is a promising diagnostic indicator of sepsis-associated PARDS. Trial registration: Clinicaltrials, ChiCTR1900023254. Registered 1 December 2018 - Retrospectively registered, http://www.clinicaltrials.gov/ChiCTR1900023254.